EFEKTIVITAS TERAPI âTRANSCUTANEOUS ELECTRIC NERVE STIMULATIONâ DALAM MENURUNKAN NYERI KRONIK PADA PENDERITA OSTEOARTHRITIS - , RISTIA ANGGARINI, Heru Subekti, S.Kep., Ns., MPH ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Rheumatic disease that mostly found in elderly is Osteoarthritis. The pain become important symptom and become reason for treatment solution. One of pain reduction that doesn't have invasive procedure and minimum side effect is TENS. Aim: This research is intended to know effectiveness of TENS 80 Hz in decrease Osteoarthritis chronic pain. Method: This is a quasi-experimental study with randomized pretest-posttest control group design. This research is held on January-April 2013 in Sleman toward OA patients minimum age 55 with samples each 8 people to TENS 80 and 100 Hz. Interventions conducted 10 sessions in two weeks for 40 minutes. Pain intensity, duration, and frequency are measure before, during and after intervention. Data analysis use ANOVA Repeated Test and Unpaired t-test for normal data distribution, also Friedman test&Post-hoc Wilcoxon and Mann Whitney for abnormal data distribution. Result: Significance of the difference in pain intensity pretest-intervenstion between treatment and control group at p=0.753 and significance of differences intervention-posttest p=0.630. Significance of the difference in pain duration pretest-intervention between the two groups was 0.753 and 0.495 for the significance of the difference in pain duration posttest-intervention. Significance of the difference in pain frequency pretest-intervenstion between the two groups at p=0.345 and significance differences intervention-posttest p=0.940. Conclusion: TENS 80 Hz and 100 Hz has the same effect in reducing pain intensity. Decrease in pain duration at TENS 80 Hz and 100 Hz groups didnât differ significantly. TENS 80 Hz and 100 Hz didnât significantly reduce